Using Time-Varying Evidence to Test Models of Decision Dynamics: Bounded Diffusion vs. the Leaky Competing Accumulator Model - Tsetsos, Konstantinos; Gao, Juan; McClelland, James L.; Usher, Marius (Frontiers in Neuroscience, 2012)
An important question in decision research is how observers weigh evidence about choice alternatives. Here we report computational and experimental studies that examine the temporal weights that observers give to evidence in a perceptual decision task and their dependence on stimulus duration and task contingencies. Previous studies, using the moving-dot stimuli, reported that observers show primacy, assigning stronger weights to earlier evidence. We show that this pattern is consistent with both a bounded-diffusion and with a leaky-competing accumulator (LCA) model with inhibition dominance. The latter model, however, predicts, for certain parameters, a switch from primacy to recency with increasing stimulus durations. Here we report two experiments, using the moving-dot stimuli, in which the evidence is temporally manipulated and the observers respond at stimulus termination. In the first experiment, the observers respond within stringent (300 ms) deadline and we obtain robust primacy effects. In the second experiment, the response deadline is relaxed (1 sec) resulting in a more equal weighting of early and late evidence. The data also shows important individual differences, which are discussed in relation to a number of computational models.